Precursor material for preparing single-crystal positive electrode material, preparation method of precursor material, single-crystal positive electrode material and secondary battery
By using hollow internal and compact external large-particle precursor materials, combined with the calcining technology of the melting element A and lithium salt or sodium salt, the problems of high cost and difficulty in sintering of single crystal positive electrode material are solved, and the problem of high cost and difficulty in sintering are achieved. High-efficiency and low-cost single crystal positive electrode material preparation.
Patent Information
- Application Number
- CN202411577564.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the precursor material of the single crystal positive electrode material has problems such as small particle size leading to high production costs and high material running, and the large particle size precursor is difficult to sinter into micron-scale single crystal particles, resulting in a degradation of battery performance.
A large-particle precursor material with hollow internal and tight external appearance is used, and the core material contains the melting elements A, such as Sr, Y, Ba and Ce, to form micron-scale single-crystal positive electrode particles with lithium or sodium salts through mixed calcination.
The preparation of single-crystal positive electrode material with low cost, low material running, no need for high temperature calcination or excessive lithium salt is achieved, and the excellent electrochemical performance of single-crystal particles is maintained.
Smart Images

Figure CN119447242A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a precursor material for preparing a single crystal positive electrode material and a preparation method thereof, a single crystal positive electrode material and a secondary battery. Background Art
[0002] The particle types of positive electrode materials for lithium-ion batteries and sodium-ion batteries include polycrystalline, quasi-single crystal and single crystal. Among them, single crystal positive electrode particles are widely used because of their unique advantages in avoiding intercrystalline cracks, stabilizing the crystal structure and reducing the side reaction problems between the particle surface and the electrolyte. The synthesis of micron-sized single crystal particles often requires reducing the size of the precursor to increase its growth activity during the sintering process, thereby obtaining a single crystal positive electrode with large primary grains and easy to disperse. However, the production cost of small-particle precursors is higher than that of large-particle precursors, and small-particle precursors are very easy to run away during the synthesis process, resulting in a significantly low yield.
[0003] Large-particle precursors are difficult to be used in the production of single-crystal cathode particles with comparable performance to small-particle precursors because their primary particles are difficult to grow into micron-sized single-crystal particles under the same sintering conditions and the dispersion between primary particles is poor. Although higher temperatures and the use of excess lithium salts or molten salts (such as LiNO3, LiOH, Li2SO4, NaCl, etc.) can sinter large-particle precursors into micron-sized single-crystal cathode particles, higher sintering temperatures cause great damage to the crystal structure, resulting in Li / O loss; the use of excess lithium salts or molten salts requires additional processing steps for the sintered material, such as water washing and post-annealing, and is likely to lead to the formation of an electrochemically inert layer on the surface, all of which inevitably reduce the capacity of the single-crystal cathode material.
[0004] Therefore, the small-particle precursors used in single crystal positive electrodes have the problems of high material loss and high production costs, and the large-particle precursors are difficult to sinter into micron-sized single crystal particles and maintain battery performance. There is an urgent need to develop a precursor material that can be used to prepare micron-sized single crystal positive electrode materials with low cost, less material loss, no need for higher sintering temperatures, and the use of excess lithium salt or molten salt.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first purpose of the present invention is to provide a precursor material for preparing a single crystal positive electrode material, which is a large-particle precursor material that is hollow inside and compact outside. At the same time, the element A in the core material has a fluxing effect, which helps the growth, cracking and fluxing of single crystal particles during high-temperature calcination, and can be sintered into micron-sized single crystal positive electrode particles without a higher sintering temperature or using excessive lithium salt or molten salt. The problem of small-particle precursors used in single crystal positive electrode materials having a lot of material loss and high production costs and large-particle precursors being difficult to sinter to form micron-sized single crystal particles and difficult to maintain battery performance is solved.
[0007] The second purpose of the present invention is to provide a method for preparing a precursor material for preparing a single crystal positive electrode material. By preparing a large-particle precursor material with a hollow core, a compact exterior and containing a flux element A, and mixing and calcining the precursor material with a lithium salt or a sodium salt, a large single crystal particle positive electrode material with excellent electrochemical properties can be obtained.
[0008] The third object of the present invention is to provide a single crystal positive electrode material with low production cost and excellent electrochemical performance.
[0009] A fourth object of the present invention is to provide a secondary battery having high capacity and excellent cycle stability.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] The present invention provides a precursor material for preparing a single crystal positive electrode material, the precursor material having a hollow structure, comprising a shell and a core material arranged on the inner surface of the shell; the core material comprising a hydroxide containing a fluxing element A, wherein A comprises at least one of Sr, Y, Ba and Ce elements; the core material further comprises at least one of Ni, Mn, Co and Fe elements; the shell comprises a hydroxide containing at least one of Ni, Mn, Co and Fe elements; the D50 particle size R3 of the precursor material satisfies 4.5μm<R3≤18μm.
[0012] Furthermore, the core material also includes at least one of the elements Zn, Mg and Al.
[0013] Furthermore, the general formula of the core material is Ni a Mn b Co c Fe d Zn e Mg f Al g A h(OH)2, wherein 0≤a<1, 0≤b<1, 0≤c<1, 0≤d≤0.55, 0≤e≤0.2, 0≤f≤0.2, 0≤g≤0.2, 0<h≤0.2, 0≤e+f+g≤0.25, a+b+c+d+e+f+g+h=1, and A includes at least one of Sr, Y, Ba and Ce.
[0014] Furthermore, the shell also includes at least one of the elements Zn, Mg and Al.
[0015] Furthermore, the general formula of the shell is Ni m Mn n Co o Fe p Zn q Mg r Al s (OH)2, wherein 0≤m<1, 0≤n<1, 0≤o<1, 0≤p≤0.55, 0≤q≤0.2, 0≤r≤0.2, 0≤s≤0.2, 0≤q+r+s≤0.25, m+n+o+p+q+r+s=1.
[0016] Furthermore, a single-side thickness R2 of the shell satisfies 0 μm<R2≤4 μm.
[0017] Furthermore, the specific surface area of the precursor material is 1 to 10 m 2 / g.
[0018] Furthermore, the tap density of the precursor material is 1.3 to 2.0 g / cm 3 .
[0019] The present invention further provides a method for preparing the precursor material for preparing single-crystalline positive electrode materials, comprising the following steps: in an air environment, adding an A-containing solution, a precipitant solution and a complexing agent solution to a base solution and performing a first precipitation reaction to obtain an inner core with a diameter of R1; wherein A includes at least one of Sr, Y, Ba and Ce elements, and the A-containing solution also includes at least one of Ni, Mn, Co and Fe elements; introducing an inert gas into the reaction system, and replacing the A-containing solution with a solution B containing at least one of Ni, Mn, Co and Fe elements, performing a second precipitation reaction and aging the inner core, and then performing solid-liquid separation to obtain the precursor material for preparing single-crystalline positive electrode materials.
[0020] Furthermore, the R1 is ≤10 μm.
[0021] Furthermore, the time of the first precipitation reaction is T1, the time of the second precipitation reaction is T2, the ratio of the molar amount of element A in the inner core to the total molar amount of metal elements in the inner core is h1, and the ratio of the molar amount of element A in the precursor material to the total molar amount of metal elements in the precursor material is h2, then 0<h2=[h1×T1 / (T1+T2)]<0.02.
[0022] Furthermore, the time of the first precipitation reaction is less than 5h.
[0023] Furthermore, the slurry obtained at the end of the first precipitation reaction is filtered, washed and dried at 100° C. for 10 hours, and the mass percentage of total metal elements in the solid obtained is 50% to 56%.
[0024] Furthermore, the second precipitation reaction time is 50 to 120 hours.
[0025] Furthermore, the mass percentage of total metal elements in the solid obtained by filtering and washing the product obtained after the second precipitation reaction is completed and drying at 100° C. for 10 hours is 58% to 63%.
[0026] Furthermore, the A-containing solution also includes at least one of the elements Zn, Mg and Al.
[0027] Furthermore, the total molar concentration of the metal elements in the A-containing solution is 0.5 to 2.5 mol / L.
[0028] Furthermore, the solution B also includes at least one of the elements Zn, Mg and Al.
[0029] Furthermore, the total molar concentration of the metal elements in the solution B is 0.5 to 2.5 mol / L.
[0030] Furthermore, the pH of the first precipitation reaction is 9.0-10.0.
[0031] Furthermore, the temperature of the first precipitation reaction is 40-75°C.
[0032] Furthermore, during the first precipitation reaction, the molar concentration of the complexing agent in the reaction system is 0.5-1.0 mol / L.
[0033] Furthermore, during the first precipitation reaction, stirring is continued at a rotation speed of 100 to 200 rpm.
[0034] Furthermore, the pH of the second precipitation reaction is 10.3-11.5.
[0035] Furthermore, the temperature of the second precipitation reaction is 40-75°C.
[0036] Furthermore, during the second precipitation reaction, the molar concentration of the complexing agent in the reaction system is 0.05 to 0.45 mol / L.
[0037] Furthermore, during the second precipitation reaction, stirring is continued at a rotation speed of 205 to 500 rpm.
[0038] Furthermore, the precipitant solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, an ammonium carbonate solution and a sodium carbonate solution.
[0039] Furthermore, the molar concentration of the precipitant solution is 2 to 11 mol / L.
[0040] Furthermore, the complexing agent solution includes at least one of an aqueous ammonia solution, an ammonium sulfate solution, a sodium citrate solution, an EDTA-2Na solution, an oxalic acid solution and an ammonium carbonate solution.
[0041] Furthermore, the molar concentration of the complexing agent solution is 0.1-5 mol / L.
[0042] The present invention further provides a single crystal positive electrode material, which is mainly formed by sintering the precursor material for preparing the single crystal positive electrode material and a lithium salt or a sodium salt.
[0043] Furthermore, the sintering temperature is ≤1000°C.
[0044] Furthermore, the single crystal positive electrode material is a single crystal particle.
[0045] Furthermore, the D50 particle size of the single crystal positive electrode material is 2 to 6 μm.
[0046] Furthermore, the tap density of the single crystal positive electrode material is 1.4 to 2.2 g / cm 3 .
[0047] The present invention also provides a secondary battery, comprising the single crystal positive electrode material.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] (1) The present invention provides a large-particle precursor material that is hollow inside and compact outside. The element A in the core material has a fluxing effect. These two aspects are helpful for the growth and cracking of single crystal particles and fluxing during high-temperature sintering. It can be sintered into micron-sized single crystal positive electrode particles without the need for a higher sintering temperature or the use of excess lithium salt or molten salt.
[0050] (2) The precursor material for preparing single crystal positive electrode material provided by the present invention has suitable specific surface area and high tap density.
[0051] (3) The precursor material for preparing single crystal positive electrode material provided by the present invention can ensure efficient lithium ion or sodium ion penetration effect and grain growth activity during high temperature sintering by controlling the thickness R2 of one side of the shell, thereby reducing the additional flux or higher sintering temperature conditions required for sintering into single crystal particles.
[0052] (4) The method for preparing the precursor material provided by the present invention is to prepare a large-particle precursor material with a hollow core, a compact exterior and containing a fluxing element A, and then mix and roast the precursor material with a lithium salt or a sodium salt to obtain a large single crystal particle positive electrode material with excellent performance.
[0053] (5) The method for preparing the precursor material provided by the present invention, by controlling the inner core diameter R1, helps to disperse the grains after the grains grow during sintering, and provides sufficient space for the independence of the single crystal grains.
[0054] (6) The method for preparing the precursor material provided by the present invention can reduce the crystallinity of the inner core by controlling the time of the first precipitation reaction. Furthermore, by controlling the time of the second precipitation reaction, the crystallinity of the outer layer or shell can be enhanced, and the inner core of the precursor can be ripened to form a hollow structure.
[0055] (7) In the method for preparing the precursor material provided by the present invention, when preparing the inner core, the low pH, low rotation speed, non-protective atmosphere environment and high complexing agent content growth environment of the first precipitation reaction system can quickly synthesize an inner core template with a large particle size and low crystallinity in a short time. In addition, when forming the outer shell, the higher pH, higher rotation speed, protective atmosphere environment, lower complexing agent content growth environment and sufficiently long growth time of the second precipitation reaction system can effectively promote the tapping, high crystallinity, high sphericity and internal hollowing of the large particle size precursor.
[0056] (8) The preparation method of the precursor material provided by the present invention utilizes the growth characteristics of the inner core and the outer shell during different precipitation reactions. A core template with low crystallinity is first formed by a rapid reaction, and then a dense portion of the outer shell is formed by subsequent crystallization growth. At the same time, a ripening mechanism occurs at the position of the inner core, so that the inner core forms a special hollow structure. This method is applicable to existing precursor production equipment and does not require the use of additional auxiliary agents.
[0057] (9) The calcination temperature required for the single crystal positive electrode material prepared by the present invention using a large particle precursor is equivalent to that of the single crystal material prepared by using a small particle precursor, and the performance of the single crystal positive electrode materials of the two are basically the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0059] Figure 1 This is a SEM cross-sectional view of the precursor material prepared in Example 1 provided by the present invention;
[0060] Figure 2 This is a SEM image of the single crystal positive electrode material obtained in Example 1 provided by the present invention;
[0061] Figure 3 This is a SEM cross-sectional view of the precursor material prepared in Comparative Example 1 provided by the present invention;
[0062] Figure 4 This is a SEM image of the positive electrode material prepared in Comparative Example 1 provided by the present invention;
[0063] Figure 5 This is a SEM image of the single crystal positive electrode material prepared in Comparative Example 2 provided by the present invention;
[0064] Figure 6 This is a SEM cross-sectional view of the precursor material prepared in Comparative Example 3 provided by the present invention;
[0065] Figure 7 This is a SEM image of the positive electrode material prepared in Comparative Example 3 provided by the present invention. DETAILED DESCRIPTION
[0066] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0067] In a first aspect, the present invention provides a precursor material for preparing a single crystal positive electrode material, wherein the precursor material has a hollow structure, that is, the interior of the precursor material is hollow.
[0068] The precursor material comprises a shell and a core material arranged on the inner surface of the shell, that is, the core material is attached to the inner wall of the shell.
[0069] It can be understood that the particle shape of the precursor material is spherical or quasi-spherical.
[0070] Wherein, the core material includes a hydroxide containing a flux element A, wherein A includes at least one of Sr, Y, Ba and Ce elements, for example, two, three or four; the core material also includes at least one of Ni, Mn, Co and Fe elements, for example, two, three or four.
[0071] The shell includes a hydroxide containing at least one element of Ni, Mn, Co, and Fe.
[0072] The D50 particle size R3 of the precursor material satisfies 4.5 μm<R3≤18 μm. Wherein, R3 includes but is not limited to any point value of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, and 18 μm, or a range value between any two of them.
[0073] In order to solve the problem that large-particle precursors are difficult to sinter into single-crystalline positive electrode particles, the present invention provides a precursor material with a microstructure that is hollow inside and dense outside, and the internal core material contains element A that acts as a flux, which helps the growth and cracking of single-crystalline particles during high-temperature calcination. There is no need to additionally increase the calcination temperature of the single-crystalline particles, and single-crystalline positive electrode materials can be obtained by sintering at conventional temperatures. This proposes a novel precursor design idea for the synthesis of single-crystalline positive electrode materials.
[0074] Specifically, in the sintering process of preparing single crystal positive electrode materials, Ce, Sr, Y, and Ba ions doped inside the precursor material can be used as flux to help the melting of primary ions, play a role in increasing the size of a particle, and can also reduce the sintering temperature to obtain a material with a stable and orderly crystal structure. The outer layer (shell) can rely on the effects of lithium salt / sodium salt and high temperature to promote the growth of primary grains, and the diffusion of Ce, Sr, Y, and Ba ions from the inside to the outside can also increase the effect of grain size. In addition, the hollow area of the inner core of the large-particle precursor not only effectively avoids relying on lithium salt / sodium salt and high temperature environment to promote the melting and growth of particles in this position, but also provides sufficient space for the mutual dispersion and independence of the grown grains. The combination of these schemes ultimately promotes the sintering of large-particle precursors to form a single-crystalline particle dispersed positive electrode material.
[0075] In some specific embodiments, the core material further includes at least one of Zn, Mg and Al elements; or two or three of them. Doping with Zn, Mg and Al elements is beneficial to promoting the structural stability of the positive electrode material.
[0076] In some specific embodiments, the general formula of the core material is Ni a Mn b Co c Fe d Zn e Mg f Al g A h (OH)2, wherein 0≤a<1, 0≤b<1, 0≤c<1, 0≤d≤0.55, 0≤e≤0.2, 0≤f≤0.2, 0≤g≤0.2, 0<h≤0.2, 0≤e+f+g≤0.25, a+b+c+d+e+f+g+h=1; A includes at least one of Sr, Y, Ba and Ce, for example, two, three or four thereof.
[0077] General formula Ni a Mn b Co c Fe d Zn e Mg f Al g A h(OH)2, a includes but is not limited to any one of 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.96, 0.98, 0.99 or any range between two of them; b includes but is not limited to any one of 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.96, 0.98, 0.99 or any range between two of them; c includes but is not limited to any one of 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0 0.8, 0.9, 0.95, 0.96, 0.98, 0.99, or any range between them; d includes but is not limited to any point value of 0, 0.01, 0.03, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.5, 0.55, or any range between them; e includes but is not limited to any point value of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2 f includes but is not limited to any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2 or any range between them; g includes but is not limited to any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2 or any range between them; h includes but is not limited to any one of 0.001, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2, or the range between any two of them; e+f+g includes but is not limited to any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2, 0.23, 0.25, or the range between any two of them.
[0078] In some specific implementations, the shell further includes at least one of the elements Zn, Mg and Al; or two or three.
[0079] In some specific embodiments, the general formula of the shell is Ni m Mnn Co o Fe p Zn q Mg r Al s (OH)2, wherein 0≤m<1, 0≤n<1, 0≤o<1, 0≤p≤0.55, 0≤q≤0.2, 0≤r≤0.2, 0≤s≤0.2, 0≤q+r+s≤0.25, m+n+o+p+q+r+s=1.
[0080] General formula Ni m Mn n Co o Fe p Zn q Mg r Al sIn (OH)2, m includes but is not limited to any one of 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.96, 0.98, 0.99 or any range between two of them; n includes but is not limited to any one of 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.96, 0.98, 0.99 or any range between two of them; o includes but is not limited to 0, 0. 1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.96, 0.98, 0.99, or any range between them; p includes, but is not limited to, 0, 0.01, 0.03, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.5, 0.55, or any range between them; q includes, but is not limited to, 0, 0.01, 0.02, 0.03, 0 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2, or any range between them; r includes but is not limited to 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2, or any range between them; s includes but is not limited to 0, 0.01, 0.02, The point value of any one of 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2, or the range value between any two of them; q+r+s includes but is not limited to the point value of any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12, 0.13, 0.15, 0.16, 0.18, 0.2, 0.23, 0.25, or the range value between any two of them.
[0081] The present invention is suitable for preparing hollow large particle precursors containing one or more elements such as Ni, Mn, Co, Fe, Zn, Mg, Al, etc. The single crystal positive electrode materials obtained from different elements can be used as different types of battery materials and have a wide range of applications.
[0082] In some specific embodiments, the single-side thickness R2 of the shell satisfies 0μm<R2≤4μm; wherein R2 includes but is not limited to any point value of 0.1μm, 0.2μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm or a range value between any two of them.
[0083] It can be understood that the above-mentioned single-side thickness R2 refers to the average thickness of the single-side shell.
[0084] In some specific embodiments, the inner diameter of the hollow structure is 3 to 10 μm, including but not limited to any point value of 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm, or a range value between any two of them.
[0085] In some specific embodiments, the specific surface area of the precursor material is 1 to 10 m 2 / g; but not limited to 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, or a range of values between them.
[0086] In some specific embodiments, the tap density of the precursor material is 1.3 to 2.0 g / cm 3 , including but not limited to 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 Any point value in or any range of values between them.
[0087] In a second aspect, the present invention provides a method for preparing the above-mentioned precursor material for preparing a single crystal positive electrode material, comprising the following steps:
[0088] First, in an air environment, an A-containing solution, a precipitant solution and a complexing agent solution are simultaneously added to the base solution to perform a first precipitation reaction to obtain a core with a diameter of R1, and the feeding reaction is stopped. Wherein, A includes at least one of Sr, Y, Ba and Ce elements. The A-containing solution also includes at least one of Ni, Mn, Co and Fe elements. The present invention adds at least one of Zn, Mg and Al elements for doping during the precursor synthesis stage, which helps to uniformly distribute such doping elements in the particles and promotes the structural stability of the positive electrode material.
[0089] It can be understood that the air environment refers to an atmosphere without any gas, that is, the atmospheric environment.
[0090] It can be understood that the above-mentioned base solution refers to a mixed solution containing a precipitant and a complexing agent.
[0091] It can be understood that the above diameter R1 refers to the average diameter of the core of the precursor.
[0092] In some specific embodiments, the method for preparing the A-containing solution includes: uniformly mixing at least one of a soluble nickel salt, a soluble manganese salt, a soluble cobalt salt and a soluble iron salt with a soluble A salt and water.
[0093] In some specific embodiments, the above-mentioned soluble nickel salt, soluble manganese salt, soluble cobalt salt, soluble iron salt and soluble A salt include but are not limited to one or more of sulfates, nitrates, acetates, chlorides, etc.
[0094] Then, an inert gas is introduced into the reaction system to expel the air present in the first precipitation reaction, and the solution containing A is replaced with a solution B containing at least one element of Ni, Mn, Co and Fe, and the feeding is continued to carry out the second precipitation reaction and the aging of the inner core until particles with a diameter of R3 are formed, and the solid and liquid are separated to obtain the precursor material for preparing a single crystal positive electrode material.
[0095] It can be understood that the inert gas includes any gas commonly used in the art, such as nitrogen, argon, etc., but is not limited thereto.
[0096] The diameter R3 refers to the average diameter of the particles, which is also the D50 particle size of the particles. That is, the average diameter or D50 particle size of the precursor material obtained for preparing the single crystal positive electrode material is R3. Among them, R3 satisfies 4.5μm<R3≤18μm.
[0097] It can be understood that replacing the solution A with a solution B containing at least one element of Ni, Mn, Co and Fe means that the solution B continues to mix and react with the precipitant solution and the complexing agent solution.
[0098] It can be understood that the above-mentioned ripening of the inner core refers to the process of continuous dissolution and recrystallization of the inner core, wherein, since the crystals constituting the inner core have low crystallinity and are unstable, they will adhere to the inner wall of the tight shell formed by the second precipitation reaction during the recrystallization process, thereby forming a hollow structure.
[0099] In some specific embodiments, the method for preparing solution B comprises: uniformly mixing at least one of a soluble nickel salt, a soluble manganese salt, a soluble cobalt salt and a soluble iron salt with water.
[0100] In some specific embodiments, the soluble nickel salt, soluble manganese salt, soluble cobalt salt and soluble iron salt include but are not limited to one or more of sulfates, nitrates, acetates, chlorides and the like.
[0101] The present invention prepares a large-particle precursor material with a hollow core, a compact exterior and containing a fluxing element A, and mixes and bakes the precursor material with a lithium salt or a sodium salt to obtain a large single-crystal particle positive electrode material with excellent performance. This solves the problem of large-particle precursors used for single-crystal positive electrode materials having a large amount of material loss and high production costs, and also solves the problem that it is difficult to form micron-sized single-crystal particles by sintering large-particle precursors, and that the use of higher temperatures and excessive lithium salts or molten salts leads to a decrease in the electrochemical performance of positive electrode materials.
[0102] In some specific embodiments, the 3<R1≤10μm, including but not limited to any point value of 10μm, 9μm, 8μm, 7μm, 6μm, 5μm, 4μm or any range value between two of them. The large size of the kernel diameter R1 helps to disperse the grains after the grains grow during sintering, and provides sufficient space for the independence of single crystal grains. When the size of the kernel R1 is small or 0, there is a dilemma between the primary particles inside, which is that they compete with each other but are difficult to grow independently. It is difficult for them to grow and disperse with each other, resulting in the kernel only forming a structure with small grains and still being a polycrystalline aggregate.
[0103] In some specific embodiments, the time of the first precipitation reaction is T1, the time of the second precipitation reaction is T2, the ratio of the molar amount of the A element in the core to the total molar amount of the metal elements in the core is h1, and the ratio of the molar amount of the A element in the precursor material to the total molar amount of the metal elements in the precursor material is h2, then 0<h2=[h1×T1 / (T1+T2)]<0.02. Wherein, the values of h2 and [h1×T1 / (T1+T2)] include but are not limited to any point value of 0.0001, 0.001, 0.002, 0.003, 0.004, 0.005, 0.008, 0.01, 0.012, 0.015, 0.018, 0.02 or the range value between any two. The amount of the A element is controlled within the above range, which is conducive to further improving the structural stability of the positive electrode material.
[0104] In some specific embodiments, the first precipitation reaction time is less than 5 hours, including but not limited to any one of 5 hours, 4 hours, 3 hours, 2 hours, and 1 hour, or any range between two of them. This can reduce the crystallinity of the inner core.
[0105] In some specific embodiments, the mass percentage of total metal elements (i.e., all metal elements) in the solid obtained after the slurry obtained at the end of the first precipitation reaction is filtered and washed and dried at 100° C. for 10 hours is 50% to 56%, including but not limited to any point value of 50%, 51%, 52%, 53%, 54%, 55%, 56% or any range value between two of them. The low total metal ion percentage can indicate that the core template obtained by the first precipitation reaction has low crystallinity, which is easy to ripen the core in the subsequent precipitation to form a hollow structure.
[0106] In some specific embodiments, the second precipitation reaction time is 50 to 120 hours, including but not limited to any one of 50 hours, 60 hours, 70 hours, 80 hours, 90 hours, 100 hours, 110 hours, and 120 hours, or any range between two of them. This can enhance the crystallinity of the outer layer or shell, and ripen the precursor core to form a hollow structure.
[0107] In some specific embodiments, the mass percentage of total metal elements (i.e., all metal elements) in the solid obtained after the second precipitation reaction is filtered and washed and dried at 100° C. for 10 hours is 58% to 63%, including but not limited to any point value of 58%, 59%, 60%, 61%, 62%, 63% or any range value between two of them. A higher total metal ion percentage can indicate that the product obtained by the second precipitation reaction has high crystallinity, indicating that the reaction time is also easy to have a maturation effect on the core template.
[0108] In some specific embodiments, the A-containing solution further includes at least one of Zn, Mg and Al elements or ions.
[0109] In some specific embodiments, the method for preparing the A-containing solution includes: uniformly mixing at least one of a soluble nickel salt, a soluble manganese salt, a soluble cobalt salt and a soluble iron salt and at least one of a soluble zinc salt, a soluble magnesium salt and a soluble aluminum salt with a soluble A salt and water.
[0110] In some specific embodiments, the soluble zinc salt, soluble magnesium salt and soluble aluminum salt include but are not limited to one or more of sulfates, nitrates, acetates, chlorides, etc. As an example, the aluminum salt may be one or more of aluminum nitrate, aluminum chloride, aluminum sulfate, sodium aluminate, etc.
[0111] In some specific embodiments, the total molar concentration of the metal elements in the solution containing A is 0.5 to 2.5 mol / L, including but not limited to any point value of 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, or a range value between any two of them.
[0112] In some specific embodiments, the solution B further comprises at least one of Zn, Mg and Al elements or ions.
[0113] In some specific embodiments, the preparation method of solution B includes: uniformly mixing at least one of a soluble nickel salt, a soluble manganese salt, a soluble cobalt salt and a soluble iron salt and at least one of a soluble zinc salt, a soluble magnesium salt and a soluble aluminum salt with water.
[0114] In some specific embodiments, the soluble zinc salt, soluble magnesium salt and soluble aluminum salt include but are not limited to one or more of sulfates, nitrates, acetates, chlorides and the like.
[0115] As an example, the aluminum salt may be one or more of aluminum nitrate, aluminum chloride, aluminum sulfate, sodium metaaluminate, and the like.
[0116] In some specific embodiments, the total molar concentration of the metal elements in the solution B is 0.5-2.5 mol / L, including but not limited to any point value of 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, or a range value between any two of them.
[0117] In some specific embodiments, the pH of the first precipitation reaction is 9.0-10.0, including but not limited to any point value of 9.0, 9.1, 9.3, 9.5, 9.6, 9.8, 10.0 or a range of values between any two of them.
[0118] In some specific embodiments, the temperature of the first precipitation reaction is 40-75°C, including but not limited to any point value of 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or a range value between any two of them.
[0119] In some specific embodiments, during the first precipitation reaction, the molar concentration of the complexing agent in the reaction system is 0.5-1.0 mol / L; including but not limited to any one of 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L or a range between any two of them.
[0120] In some specific embodiments, during the first precipitation reaction, stirring is continued at a rotation speed of 100 to 200 rpm, wherein the rotation speed includes but is not limited to any point value of 100 rpm, 120 rpm, 130 rpm, 150 rpm, 180 rpm, 200 rpm or a range value between any two of them.
[0121] When preparing the inner core, the pH of the first precipitation reaction system is low, the stirring speed is low, and the particle size increases rapidly. At this time, adding Ce, Sr, Y, and Ba ions as dopants can greatly reduce the segregation of precipitates produced by these ions during the reaction.
[0122] When preparing the inner core, the low pH, low rotation speed, non-protective atmosphere environment and high complexing agent content growth environment of the first precipitation reaction system can quickly synthesize an inner core template with larger particle size and lower crystallinity in a short time.
[0123] In some specific embodiments, the pH, molar concentration of the complexing agent and temperature of the base solution are the same as the pH, molar concentration of the complexing agent and temperature of the first precipitation reaction.
[0124] In some specific embodiments, the pH of the second precipitation reaction is 10.3-11.5, including but not limited to any point value of 10.3, 10.5, 10.8, 11.0, 11.2, 11.3, 11.5 or a range of values between any two of them.
[0125] In some specific embodiments, the temperature of the second precipitation reaction is 40-75°C, including but not limited to any point value of 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or a range value between any two of them.
[0126] In some specific embodiments, during the second precipitation reaction, the molar concentration of the complexing agent in the reaction system is 0.05-0.45 mol / L, including but not limited to any one of 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, and 0.45 mol / L, or a range between any two of them.
[0127] In some specific embodiments, during the second precipitation reaction, stirring is continued at a rotation speed of 205 to 500 rpm, wherein the rotation speed includes but is not limited to any point value of 205 rpm, 210 rpm, 220 rpm, 230 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm or a range value between any two of them.
[0128] When forming the shell, the higher pH, higher rotation speed, protective atmosphere, lower complexing agent content and sufficiently long growth time of the second precipitation reaction system can effectively promote the compaction, high crystallinity, high sphericity and internal hollowing of the large-particle precursor.
[0129] The present invention utilizes the growth characteristics of the inner core and the outer shell during different precipitation reactions, firstly forms an inner core template with low crystallinity through a rapid reaction (i.e., the first precipitation reaction), and then combines subsequent crystallization growth to form a dense outer shell portion. At the same time, a ripening mechanism occurs at the inner core position, so that the inner core forms a special hollow structure (i.e., the second precipitation reaction). The synthesis method is applicable to existing precursor production equipment and does not require the use of additional auxiliary agents.
[0130] In some specific embodiments, the precipitant solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, an ammonium carbonate solution and a sodium carbonate solution.
[0131] In some specific embodiments, the molar concentration of the precipitant solution is 2 to 11 mol / L, including but not limited to any point value of 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L or a range value between any two of them.
[0132] In some specific embodiments, the complexing agent solution includes at least one of an aqueous ammonia solution, an ammonium sulfate solution, a sodium citrate solution, an EDTA-2Na solution, an oxalic acid solution, and an ammonium carbonate solution.
[0133] In some specific embodiments, the molar concentration of the complexing agent solution is 0.1-5 mol / L, including but not limited to any one of 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or a range between any two of them.
[0134] In a third aspect, the present invention provides a single crystal positive electrode material, which is mainly formed by sintering the above-mentioned precursor material for preparing the single crystal positive electrode material with a lithium salt or a sodium salt.
[0135] That is, the precursor material is mixed with lithium salt and sintered to obtain a lithium-ion battery single crystal positive electrode material; or, the precursor material is mixed with sodium salt and sintered to obtain a sodium-ion battery single crystal positive electrode material.
[0136] Single crystal positive electrode materials can avoid intercrystalline cracks, stabilize the crystal structure, and reduce side reaction problems between the particle surface and the electrolyte.
[0137] Furthermore, the single crystal positive electrode material provided by the present invention has low cost and excellent electrochemical performance.
[0138] In some specific embodiments, the sintering temperature is ≤1000°C, including but not limited to any one of 1000°C, 900°C, 800°C, 700°C or a range between any two of them.
[0139] In some specific embodiments, the sintering holding time is 8 to 20 hours, including but not limited to any one of 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, and 20 hours, or a range between any two of them.
[0140] The calcination temperature required for the single crystal positive electrode material prepared by using the large particle precursor of the present invention is equivalent to that of the single crystal material prepared by using the small particle precursor, and the performance of the single crystal positive electrode materials of the two is basically the same.
[0141] In some specific implementations, the sintering specifically includes: pre-sintering at 300-590° C. from room temperature for 2-8 hours, and then heating to 700-1000° C. for 8-20 hours. The purpose of pre-sintering is to dehydrate the hydroxide.
[0142] In some specific embodiments, the single crystal positive electrode material is a single crystal particle.
[0143] In some specific embodiments, the D50 particle size of the single crystal positive electrode material is 2 to 6 μm, including but not limited to any point value of 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, or a range value between any two of them.
[0144] In some specific embodiments, the tap density of the single crystal positive electrode material is 1.4 to 2.2 g / cm 3 , including but not limited to 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.8g / cm 3 , 2.0g / cm 3 , 2.2g / cm 3 Any point value in or any range of values between them.
[0145] In some specific embodiments, the molar ratio of the precursor material to the lithium element or the sodium element is 1:(α+0.02-0.07), and satisfies 0.6≤α≤1.2.
[0146] In some specific embodiments, the lithium salt is one or more of lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, and lithium acetate; the sodium salt is one or more of sodium hydroxide, sodium oxide, sodium carbonate, sodium nitrate, and sodium oxalate, and the present invention is not limited to this.
[0147] In a fourth aspect, the present invention provides a secondary battery comprising the above-mentioned single crystal positive electrode material.
[0148] The battery prepared by using the precursor and the single crystal positive electrode material provided by the present invention has excellent electrochemical performance, high capacity and excellent cycle stability.
[0149] In some specific embodiments, the secondary battery includes but is not limited to a lithium ion battery and a sodium ion battery.
[0150] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0151] Example 1
[0152] The method for preparing a precursor material for preparing a single crystal positive electrode material provided in this embodiment comprises the following steps:
[0153] In an air environment, nickel sulfate, cobalt sulfate, manganese nitrate and cerium nitrate are prepared into a solution A with a total molar concentration of metal ions of 1.5 mol / L (wherein the molar ratio of Ni, Co, Mn and Ce is 0.90:0.04:0.04:0.02); nickel sulfate, cobalt sulfate and manganese nitrate are prepared into a solution B with a total molar concentration of metal ions of 1.5 mol / L (wherein the molar ratio of Ni, Co and Mn is 0.9184:0.0408:0.0408); 6 mol / L sodium hydroxide solution is prepared as a precipitant solution, and 3 mol / L ammonia solution is prepared as a complexing agent solution; before the reaction, water, the precipitant solution and the complexing agent solution are first added to a 200 L reactor and heated to make the pH of the bottom liquid in the reactor 9.2, the molar concentration of the complexing agent 0.65 mol / L, the temperature 70°C, and the stirring speed 150 rpm.
[0154] After that, the first stage precipitation reaction is carried out: the A solution, the complexing agent solution and the precipitant solution are simultaneously injected into the reactor for reaction, the reactor is maintained at a temperature of 70°C, a stable pH of 9.2, a molar concentration of the complexing agent in the reactor of 0.65 mol / L, and a rotation speed of 200 rpm for continuous stirring. After the reaction for 1 hour, an inner core with a radius of 2.5 μm (i.e., a diameter R1 = 5 μm) is obtained, and the feeding reaction is stopped at this time. After the first stage precipitation reaction is completed, a portion of the slurry obtained is taken, filtered and washed, and dried at 100°C for 10 hours, and the mass percentage of the total metal elements in the obtained solid is 53%.
[0155] Next, the second stage precipitation reaction was carried out: nitrogen was introduced (at a flow rate of 30 L / h) for 2 hours, then the solution containing A was replaced with solution B, and the feed reaction was continued (i.e., solution B, the precipitant solution and the complexing agent solution were simultaneously introduced into the reactor for reaction), the temperature in the reactor was maintained at 70°C, the pH was stabilized at 10.8, the molar concentration of the complexing agent in the reactor was 0.23 mol / L, the rotation speed was continuously stirred at 380 rpm, and after 110 hours of reaction, the solid-liquid separation was performed to obtain a precursor material with a radius of 5.5 μm (i.e., D50 particle size R3 = 11 μm). A portion of the precursor material was taken, filtered and washed, and dried at 100°C for 10 hours, and the mass percentage of the total metal elements in the obtained solid was 61%.
[0156] In this embodiment, the reaction time of the first stage precipitation reaction is T1, the ratio of the molar amount of element A in the inner core formed by the first stage precipitation reaction to the total molar amount of metal elements in the inner core is h1, the reaction time of the second stage precipitation reaction is T2, the ratio of the molar amount of element A in the precursor material formed by the second stage precipitation reaction to the total molar amount of metal elements in the precursor material is h2, wherein h2=0.00018, satisfying 0<h2=[h1×T1 / (T1+T2)]<0.02.
[0157] The precursor material for preparing the single crystal positive electrode material prepared in this embodiment has a hollow structure. The precursor material includes a shell and a core material arranged on the inner surface of the shell, wherein the general formula of the core material is Ni 0.9 Co 0.04 Mn 0.04 Ce 0.02 (OH)2, the general formula of the shell is Ni 0.9184 Co 0.0408 Mn 0.0408 (OH)2, the single-side thickness R2 of the shell is 3μm.
[0158] The specific surface area of the precursor material is 6.3 m 2 / g, the tap density of the precursor material is 1.8g / cm 3 .
[0159] Figure 1 This is a SEM cross-sectional view of the precursor material prepared in this embodiment. It can be seen that it is hollow inside.
[0160] This embodiment further provides a method for preparing a single crystal positive electrode material, comprising the following steps: mixing the above-mentioned precursor material with lithium hydroxide, wherein the molar ratio of lithium element to the precursor material is 1.07:1, then pre-burning from room temperature to 500°C for 5 hours, then heating to 830°C and roasting for 15 hours, and obtaining a single crystal positive electrode material after cooling.
[0161] The single crystal positive electrode material prepared in this embodiment has a D50 particle size of 4.5 μm and a tap density of 1.9 g / cm 3 .
[0162] Figure 2 This is a SEM image of the single crystal positive electrode material prepared in this embodiment. It can be seen that it is a single crystal particle.
[0163] Example 2
[0164] The method for preparing a precursor material for preparing a single crystal positive electrode material provided in this embodiment comprises the following steps:
[0165] In an air environment, nickel sulfate, cobalt sulfate, manganese sulfate and yttrium acetate are prepared into a solution A with a total molar concentration of metal ions of 2 mol / L (the molar ratio of Ni, Co, Mn and Y is 0.15:0.15:0.60:0.10); nickel sulfate, cobalt sulfate and manganese sulfate are prepared into a solution B with a total molar concentration of metal ions of 2 mol / L (the molar ratio of Ni, Co and Mn is 0.165:0.165:0.670); 6 mol / L sodium hydroxide solution is prepared as a precipitant solution, and 3 mol / L ammonia solution is prepared as a complexing agent solution; before the reaction, water, the precipitant solution and the complexing agent solution are added to a 200 L reactor and heated to make the pH of the bottom liquid in the reactor 9.2, the molar concentration of the complexing agent 0.5 mol / L, the temperature 60°C, and the stirring speed 100 rpm.
[0166] After that, the first stage precipitation reaction is carried out: the A solution, the complexing agent solution and the precipitant solution are simultaneously injected into the reactor for reaction, the reactor is maintained at a temperature of 60°C, a stable pH of 9.2, a molar concentration of the complexing agent in the reactor of 0.5 mol / L, and the rotation speed is continuously stirred at 160 rpm. After 4 hours of reaction, an inner core with a radius of 3.6 μm (i.e., a diameter R1 = 7.2 μm) is obtained, and the feeding reaction is stopped at this time. After the first stage precipitation reaction is completed, a portion of the slurry obtained is taken, filtered and washed, and dried at 100°C for 10 hours, and the mass percentage of the total metal elements in the obtained solid is 52%.
[0167] Next, the second stage precipitation reaction was carried out: nitrogen was introduced (flow rate was 15 L / h) for 2 hours, then the solution containing A was replaced with solution B, and the reaction was continued. The temperature in the reactor was maintained at 60°C, the stable pH was 10.7, the molar concentration of the complexing agent in the reactor was 0.1 mol / L, and the rotation speed was continuously stirred at 300 rpm. After 70 hours of reaction, the solid-liquid separation was performed to obtain a precursor material with a radius of 7.5 μm (i.e., D50 particle size R3 = 15 μm). A portion of the precursor material was taken, filtered and washed, and dried at 100°C for 10 hours, and the mass percentage of the total metal elements in the obtained solid was 60%.
[0168] In this embodiment, the reaction time of the first stage precipitation reaction is T1, the ratio of the molar amount of element A in the inner core formed by the first stage precipitation reaction to the total molar amount of metal elements in the inner core is h1, the reaction time of the second stage precipitation reaction is T2, the ratio of the molar amount of element A in the precursor material formed by the second stage precipitation reaction to the total molar amount of metal elements in the precursor material is h2, wherein h2=0.0054, satisfying 0<h2=[h1×T1 / (T1+T2)]<0.02.
[0169] The precursor material for preparing the single crystal positive electrode material prepared in this embodiment has a hollow structure. The precursor material includes a shell and a core material arranged on the inner surface of the shell, wherein the general formula of the core material is Ni 0.15 Co 0.15 Mn 0.6 Y 0.1 (OH)2, the general formula of the shell is Ni 0.165 Co 0.165 Mn 0.67 (OH)2, the single-side thickness R2 of the shell is 3.9μm.
[0170] The specific surface area of the precursor material is 7.1 m 2 / g, the tap density of the precursor material is 1.8g / cm 3 .
[0171] The preparation method of the single crystal positive electrode material provided in this embodiment includes the following steps: mixing the above-mentioned precursor material with lithium hydroxide, wherein the molar ratio of lithium element to the precursor material is 1.25:1, then pre-burning from room temperature to 500°C for 5 hours, and then heating to 940°C for 15 hours to prepare a lithium-rich single crystal positive electrode material.
[0172] The single crystal positive electrode material prepared in this embodiment has a D50 particle size of 3.2 μm and a tap density of 1.8 g / cm 3 .
[0173] Example 3
[0174] The method for preparing a precursor material for preparing a single crystal positive electrode material provided in this embodiment comprises the following steps:
[0175] In an air environment, nickel sulfate, ferrous sulfate, manganese sulfate, and strontium nitrate crystals are used to prepare a solution A with a total molar concentration of metal ions of 1.5 mol / L (the molar ratio of Ni, Fe, Mn, and Sr is 0.3:0.3:0.3:0.1); nickel sulfate, ferrous sulfate, and manganese sulfate crystals are used to prepare a solution B with a total molar concentration of metal ions of 1.5 mol / L (the molar ratio of Ni, Fe, and Mn is 0.334:0.3333:0.3333); 6 mol / L sodium hydroxide solution is used as a precipitant solution, and 1 mol / L oxalic acid solution is used as a complexing agent solution; before the reaction, water, the above-mentioned precipitant solution and the above-mentioned complexing agent solution are first added to a 200 L reactor and heated to make the pH of the bottom liquid in the reactor 10.0, the molar concentration of the complexing agent 0.8 mol / L, the temperature 50°C, and the stirring speed 100 rpm.
[0176] After that, the first stage precipitation reaction is carried out: the A solution, the complexing agent solution and the precipitant solution are simultaneously injected into the reactor for reaction, the reactor is maintained at a temperature of 50°C, the stable pH is 10.0, the complexing agent content in the reactor is 0.8 mol / L, the rotation speed is 100 rpm and the stirring is continued, and after reacting for 3 hours, an inner core with a radius of 3 μm (i.e., diameter R1 = 6 μm) is obtained, and the feeding reaction is stopped at this time. After the first stage precipitation reaction is completed, a portion of the slurry obtained is taken, filtered and washed, and dried at 100°C for 10 hours, and the mass percentage of the total metal elements in the obtained solid is 50%.
[0177] Next, the second stage precipitation reaction was carried out: nitrogen was introduced (at a flow rate of 40 L / h) for 3 hours, then the solution containing A was replaced with solution B, and the reaction was continued. The temperature in the reactor was maintained at 50°C, the stable pH was 10.7, the molar concentration of the complexing agent in the reactor was 0.2 mol / L, and the rotation speed was continuously stirred at 450 rpm. After 60 hours of reaction, the solid-liquid separation was performed to obtain a precursor material with a radius of 6.5 μm (i.e., D50 particle size R3 = 13 μm). A portion of the precursor material was taken, filtered and washed, and dried at 100°C for 10 hours. The mass percentage of the total metal elements in the obtained solid was 63%.
[0178] In this embodiment, the reaction time of the first stage precipitation reaction is T1, the ratio of the molar amount of element A in the inner core formed by the first stage precipitation reaction to the total molar amount of metal elements in the inner core is h1, the reaction time of the second stage precipitation reaction is T2, the ratio of the molar amount of element A in the precursor material formed by the second stage precipitation reaction to the total molar amount of metal elements in the precursor material is h2, wherein h2=0.0048, satisfying 0<h2=[h1×T1 / (T1+T2)]<0.02.
[0179] The precursor material for preparing the single crystal positive electrode material prepared in this embodiment has a hollow structure. The precursor material includes a shell and a core material arranged on the inner surface of the shell, wherein the general formula of the core material is Ni 0.3 Fe 0.3 Mn 0.3 Sr 0.1 , the general formula of the shell is Ni 0.334 Fe 0.333 Mn 0.333 The single-side thickness R2 of the shell is 3.5μm.
[0180] The specific surface area of the precursor material is 9.8 m 2 / g, the tap density of the precursor material is 1.9g / cm 3 .
[0181] The preparation method of the single crystal positive electrode material provided in this embodiment includes the following steps: mixing the above-mentioned precursor material with sodium hydroxide, wherein the molar ratio of the sodium element to the precursor material is 1.05:1, then pre-burning from room temperature to 500°C for 5 hours, and then heating to 1000°C for 15 hours to prepare a sodium electric single crystal positive electrode material.
[0182] The single crystal positive electrode material prepared in this embodiment has a D50 particle size of 6 μm and a tap density of 1.9 g / cm 3 .
[0183] Example 4
[0184] The method for preparing a precursor material for preparing a single crystal positive electrode material provided in this embodiment comprises the following steps:
[0185] In an air environment, nickel sulfate, manganese sulfate, zinc sulfate, and barium nitrate are used to prepare a solution A with a total molar concentration of metal ions of 1.5 mol / L (the molar ratio of Ni, Mn, Zn, and Ba is 0.2:0.6:0.07:0.13); nickel sulfate, manganese sulfate, and zinc sulfate are used to prepare a solution B with a total molar concentration of metal ions of 1.5 mol / L (the molar ratio of Ni, Mn, and Zn is 0.233:0.667:0.10); 6 mol / L sodium hydroxide solution is used as a precipitant solution, and 1 mol / L sodium citrate solution is used as a complexing agent solution; before the reaction, water, the above-mentioned precipitant solution and the above-mentioned complexing agent solution are first added to a 200 L reactor and heated to make the pH of the bottom liquid in the reactor 10, the molar concentration of the complexing agent 0.9 mol / L, the temperature 65°C, and the stirring speed 100 rpm.
[0186] After that, the first stage precipitation reaction is carried out: the A solution, the complexing agent solution and the precipitant solution are simultaneously injected into the reactor for reaction, the reactor is maintained at a temperature of 65°C, a stable pH of 10, a molar concentration of the complexing agent in the reactor of 0.9 mol / L, and the rotation speed is continuously stirred at 100 rpm. After reacting for 2 hours, an inner core with a radius of 3.2 μm (i.e., a diameter R1 = 6.4 μm) is obtained, and the feeding reaction is stopped at this time. After the first stage precipitation reaction is completed, a portion of the slurry obtained is taken, filtered and washed, and dried at 100°C for 10 hours, and the mass percentage of the total metal elements in the obtained solid is 52%.
[0187] Next, the second stage precipitation reaction was carried out: nitrogen was introduced (the flow rate was 20L / h) for 3 hours, then the solution containing A was replaced with solution B, and the feed reaction was continued. The temperature in the reactor was maintained at 65°C, the stable pH was 10.6, the molar concentration of the complexing agent in the reactor was 0.3mol / L, and the rotation speed was continuously stirred at 360rpm. After 80 hours of reaction, the solid-liquid separation was performed to obtain a precursor material with a radius of 7μm (i.e., D50 particle size R3 = 14μm). A portion of the precursor material was taken, filtered and washed, and dried at 100°C for 10 hours. The mass percentage of the total metal elements in the obtained solid was 61%.
[0188] In this embodiment, the reaction time of the first stage precipitation reaction is T1, the ratio of the molar amount of element A in the inner core formed by the first stage precipitation reaction to the total molar amount of metal elements in the inner core is h1, the reaction time of the second stage precipitation reaction is T2, the ratio of the molar amount of element A in the precursor material formed by the second stage precipitation reaction to the total molar amount of metal elements in the precursor material is h2, wherein h2=0.0032, satisfying 0<h2=[h1×T1 / (T1+T2)]<0.02.
[0189] The precursor material for preparing the single crystal positive electrode material prepared in this embodiment has a hollow structure. The precursor material includes a shell and a core material arranged on the inner surface of the shell, wherein the general formula of the core material is Ni 0.2 Mn 0.6 Zn 0.07 Ba 0.13 (OH)2, the general formula of the shell is Ni 0.233 Mn 0.667 Zn 0.1 (OH)2, the single-side thickness R2 of the shell is 3.8μm.
[0190] The specific surface area of the precursor material is 9.1 m 2 / g, the tap density of the precursor material is 1.8g / cm 3 .
[0191] The preparation method of the single crystal positive electrode material provided in this embodiment includes the following steps: mixing the above-mentioned precursor material with sodium hydroxide, wherein the molar ratio of the sodium element to the precursor material is 0.71:1, then pre-burning from room temperature to 450°C for 5 hours, and then heating to 1000°C for 15 hours to prepare a sodium electric single crystal positive electrode material.
[0192] The single crystal positive electrode material prepared in this embodiment has a D50 particle size of 5 μm and a tap density of 1.87 g / cm 3 .
[0193] Example 5
[0194] The preparation method of the precursor material for preparing single crystal positive electrode material provided in this embodiment is basically the same as that in Example 2, except that nickel sulfate, cobalt sulfate, manganese sulfate, magnesium sulfate, and yttrium acetate are used to prepare an A-containing solution with a total molar concentration of metal ions of 2 mol / L (the molar ratio of Ni, Co, Mn, Mg, and Y is 0.1:0.1:0.60:0.10:0.10).
[0195] The precursor material for preparing the single crystal positive electrode material prepared in this embodiment has a hollow structure. The precursor material includes a shell and a core material arranged on the inner surface of the shell, wherein the general formula of the core material is Ni 0.1 Co 0.1 Mn 0.6 Mg 0.1 Y 0.1 (OH)2, the general formula of the shell is Ni 0.115 Co 0.115 Mn 0.655 Mg 0.115 (OH)2, the single-side thickness R2 of the shell is 3.9μm.
[0196] The specific surface area of the precursor material is 4.1 m 2 / g, the tap density of the precursor material is 1.94g / cm 3 .
[0197] The preparation method of the single crystal positive electrode material provided in this embodiment is the same as that in embodiment 2. The single crystal positive electrode material prepared in this embodiment has a D50 particle size of 3.6 μm and a tap density of 1.77 g / cm 3 .
[0198] Example 6
[0199] The preparation method of the precursor material for preparing single crystal positive electrode material provided in this embodiment is basically the same as that in Example 2, except that nickel sulfate, cobalt sulfate, manganese sulfate, aluminum nitrate, and yttrium acetate are used to prepare an A-containing solution with a total molar concentration of metal ions of 2 mol / L (the molar ratio of Ni, Co, Mn, Al, and Y is 0.1:0.1:0.60:0.10:0.10).
[0200] The precursor material for preparing the single crystal positive electrode material prepared in this embodiment has a hollow structure. The precursor material includes a shell and a core material arranged on the inner surface of the shell, wherein the general formula of the core material is Ni 0.1 Co 0.1 Mn 0.6 Al 0.1 Y 0.1 (OH)2, the general formula of the shell is Ni 0.115 Co 0.115 Mn 0.655 Al0.115 (OH)2, the single-side thickness R2 of the shell is 3.9μm.
[0201] The specific surface area of the precursor material is 3.8 m 2 / g, the tap density of the precursor material is 1.98g / cm 3 .
[0202] The preparation method of the single crystal positive electrode material provided in this embodiment is the same as that in Example 2. The single crystal positive electrode material prepared in this embodiment has a D50 particle size of 3.3 μm and a tap density of 1.74 g / cm 3 .
[0203] Comparative Example 1
[0204] The preparation method of the precursor material provided in this comparative example is basically the same as that in Example 1, except that during the first stage precipitation reaction, the pH in the reactor is stabilized at 10.8. Figure 3 This is a SEM cross-sectional view of the precursor material obtained in this comparative example, and it can be seen that the hollow structure area is very small. The single-side thickness R2 of the shell is 4.5 μm.
[0205] The preparation method of the positive electrode material provided in this comparative example is the same as that of Example 1. Figure 4 The SEM image of the positive electrode material obtained in this comparative example shows that the positive electrode material obtained by sintering can only be partially decomposed into a single crystal morphology, and most of it is agglomerated non-single crystal particles.
[0206] Comparative Example 2
[0207] The preparation method of the precursor material provided in this comparative example is the same as that of comparative example 1.
[0208] The preparation method of the single crystal positive electrode material provided in this comparative example is basically the same as that of comparative example 1, except that the following sintering system is adopted: first pre-sintering from room temperature to 500°C for 5h, and then heating to 880°C for 15h.
[0209] Figure 5 is a SEM image of the single crystal positive electrode material prepared in this comparative example. By comparing comparative example 1 and comparative example 2 ( Figure 4 and Figure 5 ) It can be found that although completely dispersed single crystal particles can be obtained by continuing to increase the sintering temperature, their electrical properties are seriously reduced (see Table 1).
[0210] Comparative Example 3
[0211] The preparation method of the precursor material provided in this comparative example is basically the same as that in Example 1, except that: the first stage precipitation reaction is carried out under a nitrogen atmosphere (the inlet gas flow rate is 15 L / h), and the pH in the reactor is stabilized at 11.5 during the first stage precipitation reaction; at the same time, the pH in the reactor is stabilized at 11.0 during the second stage precipitation reaction. Figure 6 This is a SEM cross-sectional view of the precursor material prepared in this comparative example. It can be seen that it does not have a hollow structure.
[0212] The preparation method of the positive electrode material provided in this comparative example is the same as that of Example 1. Figure 7 The SEM image of the positive electrode material prepared in this comparative example shows that the particles still appear as large polycrystalline particles after sintering and are difficult to be cracked into single crystal particles.
[0213] By comparing Example 1 and Comparative Examples 1 to 3, it can be seen that the inner core is hollow and the shell thickness is within a certain range, which can ensure that single crystal positive electrode particles are sintered and obtain excellent electrochemical performance.
[0214] Experimental example
[0215] Lithium-ion battery positive electrode material performance data test: The lithium battery positive electrode materials prepared in the above embodiments and comparative examples are dispersed in NMP solvent with conductive carbon black and binder PVDF in a mass ratio of 9.0:0.5:0.5, and then coated on an aluminum sheet. After cutting, they are made into circular positive electrode sheets for use. In a glove box, the positive electrode sheet is combined with a lithium sheet, a polypropylene diaphragm, and a LiPF6 electrolyte to form a button cell. Then, an electrical performance tester is used to perform charge and discharge tests on each button cell to evaluate its electrical performance. The test voltage range of embodiment 1 and comparative examples 1 to 3 is 2.8 to 4.3V, and the test voltage range of embodiment 2, embodiment 5, and embodiment 6 is 2.0 to 4.8V. The test results are shown in Table 1.
[0216] Performance data test of sodium ion battery positive electrode material: The sodium electric single crystal positive electrode material obtained in the above-mentioned Examples 3 to 4 is dispersed in NMP solvent with the conductive agent conductive carbon black and the binder PVDF in a mass ratio of 9.0:0.5:0.5, and then coated on an aluminum sheet, and cut into a circular positive electrode sheet for use. In a glove box, the positive electrode sheet is combined with a lithium sheet, a glass fiber filter paper type diaphragm, and a NaPF6 electrolyte to form a button cell. Then, an electrical performance tester is used to perform charge and discharge tests on each button cell to evaluate its capacity, and the test voltage range is 2.0 to 4.0V. The test results are shown in Table 1.
[0217] Table 1 Electrochemical performance test results of each battery
[0218]
[0219] It can be seen from Table 1 that the single crystal positive electrode particles prepared in Example 1 have higher capacity and cycle stability, while the cycle stability and capacity of the positive electrode materials obtained in Comparative Examples 1 to 3 are lower than those of the lithium battery single crystal positive electrode material in Example 1. At the same time, the lithium battery single crystal positive electrode materials prepared in Examples 2, 5 and 6 also have good electrochemical properties.
[0220] Furthermore, the sodium electric single crystal positive electrode materials prepared in Examples 3 to 4 also have good electrochemical properties.
[0221] In summary, the large-particle precursor material with a hollow interior and a compact exterior provided by the present invention can be mixed and calcined with a lithium salt or a sodium salt to obtain a single-crystal particle positive electrode material with excellent electrical properties, and the battery made using the single-crystal positive electrode material has a high capacity and good cycle stability.
[0222] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A precursor material for preparing a single crystal positive electrode material, characterized in that: The precursor material has a hollow structure, and the precursor material comprises a shell and a core material arranged on the inner surface of the shell; The core material includes a hydroxide containing a flux element A, wherein A includes at least one of Sr, Y, Ba and Ce elements; the core material also includes at least one of Ni, Mn, Co and Fe elements; The shell includes a hydroxide containing at least one element of Ni, Mn, Co and Fe; The D50 particle size R3 of the precursor material satisfies 4.5 μm<R3≤18 μm.
2. The precursor material for preparing a single crystal positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The core material further includes at least one of Zn, Mg and Al elements; (2) The general formula of the core material is Ni a Mn b Co c Fe d Zn e Mg f Al g A h (OH)2, wherein 0≤a<1, 0≤b<1, 0≤c<1, 0≤d≤0.55, 0≤e≤0.2, 0≤f≤0.2, 0≤g≤0.2, 0<h≤0.2, 0≤e+f+g≤0.25, a+b+c+d+e+f+g+h=1, and A includes at least one of Sr, Y, Ba and Ce; (3) The shell further includes at least one of Zn, Mg and Al elements; (4) The general formula of the shell is Ni m Mn n Co o Fe p Zn q Mg r Al s (OH)2, wherein 0≤m<1, 0≤n<1, 0≤o<1, 0≤p≤0.55, 0≤q≤0.2, 0≤r≤0.2, 0≤s≤0.2, 0≤q+r+s≤0.25, m+n+o+p+q+r+s=1; (5) The thickness R2 of one side of the shell satisfies 0 μm<R2≤4 μm; (6) The specific surface area of the precursor material is 1 to 10 m 2 / g; (7) The tap density of the precursor material is 1.3 to 2.0 g / cm 3 .
3. The method for preparing a precursor material for preparing a single crystal positive electrode material according to claim 1 or 2, characterized in that: The steps include: In an air environment, an A-containing solution, a precipitant solution and a complexing agent solution are added to a base solution and a first precipitation reaction is performed to obtain a core with a diameter of R1; wherein A includes at least one of Sr, Y, Ba and Ce elements, and the A-containing solution also includes at least one of Ni, Mn, Co and Fe elements; An inert gas is introduced into the reaction system, and the solution containing A is replaced with a solution B containing at least one element of Ni, Mn, Co and Fe, a second precipitation reaction and aging of the inner core are carried out, followed by solid-liquid separation to obtain the precursor material for preparing a single crystal positive electrode material.
4. The method for preparing a precursor material for preparing a single crystal positive electrode material according to claim 3, characterized in that: At least one of the following conditions is met: (1) R1≤10 μm; (2) The time of the first precipitation reaction is T1, the time of the second precipitation reaction is T2, the ratio of the molar amount of element A in the inner core to the total molar amount of metal elements in the inner core is h1, and the ratio of the molar amount of element A in the precursor material to the total molar amount of metal elements in the precursor material is h2, then 0<h2=[h1×T1 / (T1+T2)]<0.
02.
5. The method for preparing a precursor material for preparing a single crystal positive electrode material according to claim 3, characterized in that: At least one of the following conditions is met: (1) The first precipitation reaction time is less than 5 hours; (2) The slurry obtained at the end of the first precipitation reaction is filtered, washed, and dried at 100° C. for 10 hours to obtain a solid material having a mass percentage of total metal elements of 50% to 56%; (3) The second precipitation reaction time is 50 to 120 hours; (4) After the second precipitation reaction, the product obtained is filtered, washed and dried at 100° C. for 10 h. The mass percentage of total metal elements in the obtained solid is 58% to 63%.
6. The method for preparing a precursor material for preparing a single crystal positive electrode material according to claim 3, characterized in that: At least one of the following conditions is met: (1) The A-containing solution further includes at least one of Zn, Mg and Al elements; (2) the total molar concentration of the metal elements in the A-containing solution is 0.5 to 2.5 mol / L; (3) The solution B further includes at least one of Zn, Mg and Al elements; (4) The total molar concentration of the metal elements in the solution B is 0.5 to 2.5 mol / L.
7. The method for preparing a precursor material for preparing a single crystal positive electrode material according to claim 3, characterized in that: At least one of the following conditions is met: (1) The pH of the first precipitation reaction is 9.0 to 10.0; (2) the temperature of the first precipitation reaction is 40 to 75° C.; (3) During the first precipitation reaction, the molar concentration of the complexing agent in the reaction system is 0.5 to 1.0 mol / L; (4) During the first precipitation reaction, stirring is continued at a speed of 100 to 200 rpm; (5) The pH of the second precipitation reaction is 10.3 to 11.5; (6) The temperature of the second precipitation reaction is 40 to 75° C.; (7) During the second precipitation reaction, the molar concentration of the complexing agent in the reaction system is 0.05 to 0.45 mol / L; (8) During the second precipitation reaction, stirring is continued at a rotation speed of 205 to 500 rpm.
8. The method for preparing a precursor material for preparing a single crystal positive electrode material according to claim 3, characterized in that: At least one of the following conditions is met: (1) the precipitant solution comprises at least one of a sodium hydroxide solution, a potassium hydroxide solution, an ammonium carbonate solution and a sodium carbonate solution; (2) The molar concentration of the precipitant solution is 2 to 11 mol / L; (3) the complexing agent solution comprises at least one of an aqueous ammonia solution, an ammonium sulfate solution, a sodium citrate solution, an EDTA-2Na solution, an oxalic acid solution and an ammonium carbonate solution; (4) The molar concentration of the complexing agent solution is 0.1 to 5 mol / L.
9. A single crystal positive electrode material, characterized in that: It is mainly formed by sintering the precursor material for preparing the single crystal positive electrode material as claimed in claim 1 or 2 with a lithium salt or a sodium salt; Preferably, the sintering temperature is ≤1000°C; Preferably, the single crystal positive electrode material is a single crystal particle; Preferably, the D50 particle size of the single crystal positive electrode material is 2 to 6 μm; Preferably, the tap density of the single crystal positive electrode material is 1.4 to 2.2 g / cm 3 .
10. A secondary battery, characterized in that: Comprising the single crystal positive electrode material as claimed in claim 9.